Development of Historical Educational Tourism Packages at Monumen Nasional as an Urban Tourism Attraction - Satria Hakkan R. Arisakti; Rosianna Sianipar; Meitolo Hulu (Sean Institute, 2026)
Monumen Nasional (Monas) is one of Jakarta’s major urban tourism attractions that functions not only as a historical landmark but also as an educational destination representing Indonesia’s struggle for independence and national identity. However, the development of integrated historical educational tourism packages at Monas remains limited. Therefore, this study aims to identify the educational tourism potential of Monas and explore opportunities for developing historical educational tourism packages that can improve visitor experiences and historical awareness. This study employed a qualitative descriptive method. Data were collected through in-depth interviews with a Monas service staff member as the key informant, supported by observations and documentation. The collected data were analyzed through data reduction, categorization, interpretation, and conclusion drawing. The findings indicate that Monas has strong potential as a historical educational tourism destination through its historical value, museum collections, educational facilities, and guided tour services that enhance visitor engagement and learning experiences.